THE DROHOBYCH DEESIS ICONS OF THE SECOND PART OF THE FIFTEENTH CENTURY (THE STYLE OF THE WORKSHOP AND ICON PAINTERS’ MANNERS) - Сьомак, О. Ю. (Art and Design, 2023)
The purpose of this research was to analyze the artistic and stylistic features of the fifteenth century Deesis icons preserved in the Church of the Elevation of the Holy Cross in Drohobych, to characterize these icons’ stylistic lines and to single out the masters’ manner. Methodology. The research used a factual-descriptive method (highlighting the features of the iconography of the researched works); methods of formal and stylistic analysis (revealing the artistic specificity of iconographic images); method of comparative analysis; method of generalization (formulation of conclusions for this article). Results. The stylistic similarity and artistic features of the works included by the researchers in the circle of artworks related to the Drohobych Deesis were evaluated. The significant features of conventionally defined Belz-Drohobych workshop’s style have been formulated. An artistic-stylistic and comparative analysis of six Deesis images from Drohobych was carried out. The difference in the manner of icon painting was revealed. The professional level’s imbalance of the investigated icons was determined. There was offered the hypothesis about the number of craftsmen who made six preserved icons from Drohobych Deesis (there could be at least four of them). Three stylistic lines were also noted in the studied Deesis fragment: hieratic (icon of St. Archangel Michael), expressive (Saint Nicholas and Apostle Peter), harmonious (St. John the Baptist and St. Paul). Scientific novelty is provided by artistic, stylistic and comparative analysis of the preserved icons of the Drohobych Deesis in accordance with the identified manners of the icon painters and general style of the Belz-Drohobych workshop. Practical significance. The results of the analysis executed can be added to the materials for studying the history of the icon painting from Ukrainian lands in the Middle Ages and can be used to prepare an artistic and stylistic analysis of icon painting.